Shopping Value Resonance of Household Appliance and Purchase Intentions in E-Commerce - Makmur Sujarwo; Farida Indriani (Journal of Economics, Business, and Accountancy Ventura, 2021)
This study investigates shopping value resonance as a novelty concept that can bridge monetary promotion to purchase intentions on e-commerce platforms. Previous research has revealed that monetary promotion does not affect purchase intentions. The data was collected through a survey of 426 respondents who had shopped online in the form of home appliances and domiciled in Central Java, Indonesia. The data is analyzed using the Structural Equation Model PLS. The results show that monetary promotion has a significant and positive effect on purchase intention and shopping value resonance. Furthermore, shopping value resonance positively affects purchase intention. All the hypotheses are confirmed. The role of shopping value resonance as a mediation of monetary promotion and purchase intention is proven. Companies engaged in e-commerce can increase monetary promotion (e.g., discounts) through shopping value resonance, so that customer shopping on e-commerce is more comfortable and fun. This will have an impact on increasing purchase intentions. The findings suggest the need for companies to create monetary added value in theirpromotional activities considered useful by their customers.